Identification of a bioactive core sequence from human laminin and its applicability to tissue engineering. (December 2015) - Yeo, In-Sung; Min, Seung-Ki; Kang, Hyun Ki; Kwon, Taek-Ka; Jung, Sung Youn; Min, Byung-Moo
Abstract: Finding bioactive short peptides derived from proteins is a critical step to the advancement of tissue engineering and regenerative medicine, because the former maintains the functions of the latter without immunogenicity in biological systems. Here, we discovered a bioactive core nonapeptide sequence, PPFEGCIWN (residues 2678–2686; Ln2-LG3-P2-DN3), from the human laminin α2 chain, and investigated the role of this peptide in binding to transmembrane proteins to promote intracellular events leading to cell functions. This minimum bioactive sequence had neither secondary nor tertiary structures in a computational structure prediction. Nonetheless, Ln2-LG3-P2-DN3 bound to various cell types as actively as laminin in cell adhesion assays. The in vivo healing tests using rats revealed that Ln2-LG3-P2-DN3 promoted bone formation without any recognizable antigenic activity. Ln2-LG3-P2-DN3-treated titanium (Ti) discs and Ti implant surfaces caused the enhancement of bone cell functions in vitro and induced faster osseointegration in vivo, respectively. These findings established a minimum bioactive sequence within human laminin, and its potential application value for regenerative medicine, especially for bone tissue engineering.